2017
DOI: 10.18632/oncotarget.16650
|View full text |Cite
|
Sign up to set email alerts
|

Identification of JL1037 as a novel, specific, reversible lysine-specific demethylase 1 inhibitor that induce apoptosis and autophagy of AML cells

Abstract: Lysine-specific demethylase 1 (LSD1) has been recognized as a potential therapeutic target for acute myeloid leukemia (AML). Herein, we identified a novel LSD1 inhibitor, JL1037, via Computer Aided Drug Design technology. JL1037 is a potent, selective and reversible LSD1 inhibitor with IC50s of 0.1 μM and >1.5 μM for LSD1 and monoamine oxidases A/B (MAO-A/B), respectively. Treatment of THP-1 and Kasumi-1 cell lines with JL1037 resulted in dose dependent accumulation of H3K4me1 and H3K4me2, the major substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…It is clear that LSD1 inhibition may have antileukemic efficacy against multiple AML subtypes driven by other mutations. [36][37][38] For this reason, it will be important to determine if similar effects on chromatin dynamics are seen and whether similar TF networks are engaged when non-MLL-rearranged AML cells are treated with GSK-LSD1. Consistent with this, a previous study demonstrated that knockdown of PU.1 modulates LSD1 inhibitor sensitivity in a non-MLL-rearranged human acute erythroid leukemia cell line.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that LSD1 inhibition may have antileukemic efficacy against multiple AML subtypes driven by other mutations. [36][37][38] For this reason, it will be important to determine if similar effects on chromatin dynamics are seen and whether similar TF networks are engaged when non-MLL-rearranged AML cells are treated with GSK-LSD1. Consistent with this, a previous study demonstrated that knockdown of PU.1 modulates LSD1 inhibitor sensitivity in a non-MLL-rearranged human acute erythroid leukemia cell line.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly supported the idea that the autophagy pathway regulated by LSD1 was independent of BECN-1 and different from the autophagy process induced by starvation. Inhibition of LSD1 in AML cells, using the JL1037 inhibitor, provoked LC3B-II and autophagosome accumulation [72]. Moreover, combination of JL1037 with CQ favored apoptosis in this cell model.…”
Section: Lsd1 (Lysine-specific Demethylase-1) Negatively Regulates Aumentioning
confidence: 81%
“…Moreover, a high expression of LSD1 in neuroblastoma was correlated with poor prognosis [74]. Similarly, the expression of LSD1 was also increased in acute myeloid leukemia [72]. In neuroblastoma SH-SY5Y cells, inhibition of LSD1, using chemical inhibitors (TCP or SP2509), blocked LSD1 recruitment onto the SESN2 (sestrin2) promoter and induced its expression.…”
Section: Lsd1 (Lysine-specific Demethylase-1) Negatively Regulates Aumentioning
confidence: 99%
“…In leukaemia cell lines, there appears to be synergism between HDAC and LSD1 inhibitors which supports a clinical trial for further exploration [15]. More recently, a study describes a novel, specific, reversible lysine-specific demethylase 1 inhibitor JL1037 that induce apoptosis in cell lines as well as primary cells from AML patients [60]. Preclinical data have prompted multiple phase I trials using either irreversible LSD1 inhibitors such as GSK2879552 as a single agent or tranylcypromine in combination with ATRA (NCT02177812 and NCT02261779 at https://clinicaltrials.gov/, respectively).…”
Section: Lsd1 Inhibitorsmentioning
confidence: 91%